Special External Effects on Fluvial System Evolution - Vandenberghe, Jef (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Rivers are an excellent witness of the dynamics affecting Earth's surface due to their sedimentary products and morphological expression, which may be considered as fluvial archives. Until now, the focus has been on evaluating the general impact of individual external factors. However, the importance of the specific environmental characteristics of these factors has become increasingly recognized, as highlighted in recent case studies. For example, the effects of regional climate, differentiated topography and vegetation, and frozen ground appear to play an essential role in the evolution of the fluvial system. Integration of such environmental conditions in the processes that were active within the complex fluvial system will open new perspectives in our progressive understanding of the evolution of landscape form, ecology, sediment fluxes, and hydrology of the system within the framework of the external drivers such as tectonics, general climate, and human activity. This is an appealing challenge that we wish to address in the present Special Issue under the aegis of the Fluvial Archives Group (FLAG).